The Effect of Dosage and Time of Application Potassium Fertilizer on Growth of Bidara (Ziziphus Rotundifolia) - Wayan Rawiniwati; Yenisbar Yenisbar (Universitas Nasional Jakarta, 2023)
This research aimed to analyze the effect of dosage and time of application and potassium fertilizer to bidara plants’ (Ziziphus rotundifolia) growth. This research was arranged by Split Plot design in a Randomized Complete Block Design (RCBD). The Factor of Potassium time of application, that were during planting, 2 weeks after planting; 4 weeks after planting; 6 weeks after planting, was as the main plot, while the potassium fertilizer dosage of (K2O) 0 kg ha-1, 60 kg ha-1, 120 kg ha-1, 180 kg ha-1 as secondary plot. The results showed that the time of application of Potassium fertilizer had an effect on the height of the best Bidara at the age of 2 week after planting. The 60 kg K2O ha-1 dosage can increase plant height from 2 week after aplication to 10 week after aplication. The applications of 4 week after planting produced in a higher number of shoots than applications at 2 or 6 week after planting. The fertilizer application at 6 weeks after planting showed the highest fresh leaf weight and dry leaf weight which were 50,631 g and 20,900 g and the lowest in application 2 weeks after planting were 24,263 g and 12,925 g. The fertilizer dosage as much as 60 kg ha-1 produced the highest dry weight which 18,069 g. Fertilizing as much as 180 kg ha-1, showed the highest root fresh weight of at 12,757 g, compared to the control (8,900 g). The Potassium application of 6 week after planting produced the longest root growth (20,500 cm) compared to other treatments.